Effects of high-rate pulse trains on electrode discrimination in cochlear implant users. - Runge-Samuelson CL (Trends in Amplification, 2009)
Overcoming issues related to abnormally high neural synchrony in response to electrical stimulation is one aspect in improving hearing with a cochlear implant. Desynchronization of electrical stimuli have shown benefits in neural encoding of electrical signals and improvements in psychophysical tasks. In the present study, 10 participants with either CII or HiRes 90k Advanced Bionics devices were tested for the effects of desynchronizing constant-amplitude high-rate (5,000 Hz) pulse trains on electrode discrimination of sinusoidal stimuli (1,000 Hz). When averaged across the sinusoidal dynamic range, overall improvements in electrode discrimination with high-rate pulses were found for 8 of 10 participants. This effect was significant for the group (p = .003). Nonmonotonic patterns of electrode discrimination as a function of sinusoidal stimulation level were observed. By providing additional spectral channels, it is possible that clinical implementation of constant-amplitude high-rate pulse trains in a signal processing strategy may improve performance with the device.